Genetic diversity and population structure of three Hydroides species (Sedentaria, Serpulidae) in the Persian Gulf and Gulf of Oman, with the possible indication of heteroplasmy. Issue 8 (17th November 2021) - Pazoki, Samaneh; Rahimian, Hassan; Struck, Torsten H.
Abstract : The Persian Gulf, an enclosed sea connected to the Gulf of Oman through the narrow Strait of Hormuz, is known as the world's hottest sea. Owing to its harsh environmental conditions, genetic isolation has been proposed for the Gulf's biota. During the present study, population genetic and phylogeographic analyses were carried out focusing on potential barriers to dispersal in some polychaete populations between the Persian Gulf and the Gulf of Oman. Ninety-three specimens from three defined spatial populations of three Hydroides species, H . bulbosa, H . elegans and H . operculata, were sequenced for regions of two nuclear ribosomal (18S and ITS2) and two mitochondrial (COI and Cyt-b) genes to compare the genetic structure among the sampled populations. Haplotype networks of the three species showed no significant genetic differentiation and were consistent with their geographic distribution patterns. Population genetic analyses such as pairwise FST, nucleotide diversity and neutrality tests revealed some levels of intraspecific genetic diversities, suggesting different demographic histories. The genetic diversity observed in the more conservative genes (18S, Cyt-b, COI) in populations of H . elegans and H . operculata could reflect a more diverse genetic structure along their entire distribution range unlike the endemic species, H. bulbosa that presented a unique haplotype for each of those genes. Using Extended Bayesian Skyline plot analyses, populations of H. bulbosa and H. operculata showed signs of recent demographic expansion within the post-glacial transgression time frame of the Persian Gulf, while populations of H. elegans remained relatively constant. Another finding of the present study is the possible indication of heteroplasmy in H . elegans where two distinct mitochondrial lineages with about 11% of genetic divergence seem to coexist in the same individuals. We discuss also the alternative explanation of NUMTs (nuclear mitochondrial DNA), but regard it as substantially less likely.